PENENTUAN KOLABORASI PENELITIAN DAN DISTRIBUSI PENGARANG PADA JURNAL TEKNOLOGI INDONESIA (THE DETERMINATIONS OF RESEARCH COLLABORATION AND AUTHORS DISTRIBUTION IN THE JURNAL TEKNOLOGI INDONESIA) - Natakusumah, Engkos (BACA: Jurnal Dokumentasi dan Informasi, 2014)
This study aims to determine of research collaboration and authors distribution based on the data and informationmentioned in the Jurnal Teknologi Indonesia (JTI) during 5 years, from 2007 up to 2011. To reach this aims, theresearch uses methodology of bibliometric analysis to analyse the citation appeared in every last page of the articlepublished in the JTI; including distribution of articles each year, the number of contributors, the authorship, thedistribution of article languages, the single and many authors who wrote write the articles, the number of documentcited by outhors, and average number of references in an article. The bibliometrics data come from 80 articles,ranging from volume 30 up to volume 34. Then the data are tabulated, analysed and described for the purpose tomake conclusion of the research. The results show that there are domination of publication contribution by auhtors’collaboration in the journal, have significant range of research collaboration and have high rank of publication by 4researchers of 7, 6 and 5 articles published.